Hypertension, diabetes and obesity are associated with lower cognitive performance in community-dwelling elderly: Data from the FIBRA study - Monalisa Fernanda Bocchi de Oliveira; Mônica Sanches Yassuda; Ivan Aprahamian; Anita Liberalesso Neri; Maria Elena Guariento (Dementia & Neuropsychologia)
ABSTRACT. Background: Systemic hypertension (SH), diabetes mellitus (DM) and abdominal obesity may negatively impact cognitive performance. Objective: To evaluate the association between SH, DM and abdominal obesity and cognitive performance among cognitively unimpaired elderly. Methods: A cross-sectional study of individuals aged 65+ from seven Brazilian cities was conducted. SH and DM diagnoses were self-reported and abdominal circumference was objectively measured. Individuals who scored below the education-adjusted cutoff scores on the Mini-Mental State Examination (MMSE) were excluded. Results: Among 2,593 elderly, 321 (12.38%) had SH, DM and abdominal obesity concomitantly (Group I) and 421 (16.23%) had none of the three diseases (Group II). Group I had a higher proportion of individuals that were women, aged 70-74 years, illiterate and with lower income. Group I had a higher number of participants with low cognitive performance (28.04% vs. 17.58% in Group II). Variables associated with poor cognitive performance were: female gender (OR: 2.43, p < 0.001); and lower education (OR: 0.410, p < 0.001). The presence of the three diseases and age were not significant in the education-adjusted model. Conclusion: There was an association between cognition and the presence of SH, DM and obesity. However, education seems to be decisive in determining cognitive performance in the presence of these three conditions.